Effectiveness of an intervention in children between 5 and 11 years old with deforming oral habits (Revista Nacional de Odontología, 2017)
Introduction: The who states “that deforming oral habits are a frequent health problem in children.” Aim: To evaluate the effectiveness of an intervention carried out in schoolchildren of 5-11 years of age with deforming oral habits in the municipalities of Cienfuegos, Cumanayagua, Abreu and Lajas, Cuba. Methods: Quasi-experimental study with before and after intervention in a child population between 5 and 11 years old, in the period between January 2013 and September 2015. The different types of habits andanomalies present in each child were identified; the Para Sonreír Feliz program was applied weekly. A knowledge survey was applied to children, parents and educators, before and after taking educational, preventive and therapeutic actions. Results: 64.06 % of the deforming habits were eradicated (the most frequent being protractile tongue, baby bottle sucking, and nail biting), and there was a reduction in dentomaxillofacial anomalies. The levelof knowledge of children, parents and educators increased at the end of the intervention. Conclusions: The intervention was effective in reducing deforming habits and dentomaxillofacial anomalies, as well as for the satisfactory results in the level of knowledge about this entity, a health problem that can be prevented early to improve harmony in the components of the stomatognathic apparatus.
Keywords: evaluation; efficacy-effectiveness of interventions; dental health education; lingual habits; malocclusion; child